2023
DOI: 10.17507/jltr.1406.14
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Improvement of Speaking Skills Among Jordanian EFL Learners

Mohamad Ahmad Saleem Khasawneh

Abstract: The purpose of this research was to investigate the factors affecting the improvement of speaking skills among Jordanian students of English as a foreign language. This objective was reached by concentrating on educational tools, instructional strategies, and the mistakes made by students that have an impact on their skill to speak English from the perspective of students at Irbid National University and Jadara University. 316 students took part in this research project as part of the sample. In this study, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Students, still have a problem in mastering the language. Learning a language can done well if the learners are enjoy the class, and interested in challenging themselves (Khasawneh, 2023). As we know in learning the English language, four skills of language should be learned by the students, they are listening skills, speaking skills, reading skills, and writing skills.…”
Section: Discussionmentioning
confidence: 99%
“…Students, still have a problem in mastering the language. Learning a language can done well if the learners are enjoy the class, and interested in challenging themselves (Khasawneh, 2023). As we know in learning the English language, four skills of language should be learned by the students, they are listening skills, speaking skills, reading skills, and writing skills.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many issues regarding students' English speaking skills in the Vietnamese context. Interestingly, Khasawneh (2023) suggested that students should learn English speaking through conversation and authentic contexts so that facilitation could be made optimal through teaching language communication. Within this aspect, using an AI voice chatbot to provide a conversation environment between students and an AI agent is expected to be useful as AI voice chatbots were reported by Kim et al (2019) that they could speak with users in native English, providing authentic inputs.…”
Section: Literature Reviewmentioning
confidence: 99%